Color Error in the Digital Camera Image Capture Process. - Penczek, John; Boynton, Paul; Splett, Jolene (Journal of Digital Imaging, 2014)
The color error in images taken by digital cameras is evaluated with respect to its sensitivity to the image capture conditions. A parametric study was conducted to investigate the dependence of image color error on camera technology, illumination spectra, and lighting uniformity. The measurement conditions were selected to simulate the variation that might be expected in typical telemedicine situations. Substantial color errors were observed, depending on the measurement conditions. Several image post-processing methods were also investigated for their effectiveness in reducing the color errors. The results of this study quantify the level of color error that may occur in the digital camera image capture process, and provide guidance for improving the color accuracy through appropriate changes in that process and in post-processing.